2022
DOI: 10.3389/fsurg.2021.705174
|View full text |Cite
|
Sign up to set email alerts
|

Role of Breast-Conserving Surgery on the National Health System Economy From and to SARS-COVID-19 Era

Abstract: Day surgery breast-conserving surgery (DS-BCS) is a surgical approach applied in many specialized breast surgery departments. This study demonstrates the benefits of this approach from the perspectives of patients and of the Hospital/National Health System compared to ordinary breast-conserving surgery (ORD-BCS) under general anesthetic. A comparison of costs and diagnosis-related group (DRG) reimbursement demonstrated improved cost-effectiveness in DS-BCS compared to ORD-BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The patients included in the ordinary surgical procedure group were those who did not satisfy the day surgery criteria (30%). During their study, no major complications were reported, and there were no statistically significant differences in patient characteristics between the two groups (p>0.05) (7). The cost of ordinary surgery to the National Health System (NHS) was 48,135 €, whereas that of day surgery was 53,118 €.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The patients included in the ordinary surgical procedure group were those who did not satisfy the day surgery criteria (30%). During their study, no major complications were reported, and there were no statistically significant differences in patient characteristics between the two groups (p>0.05) (7). The cost of ordinary surgery to the National Health System (NHS) was 48,135 €, whereas that of day surgery was 53,118 €.…”
Section: Resultsmentioning
confidence: 96%
“…The study's benchmark was the comparison between the costs incurred by a DS-BCS treatment and those incurred by an ORD-BCS treatment. Based on the assumption that the DS regimen also guarantees a high degree of safety and quality of treatment, it not only reduces the costs and the shortening of waiting time for the patient, but also increases the efficiency and productivity of the healthcare system, i.e., the number of patients undergoing treatment (7,18). Demonstrating this, Buonomo et al managed to maximize the utility of the hospital health service during the pandemic with awake breast surgery and, at the same time, minimize the risk of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…According to the higher risk of breast cancer diagnosis underestimation, we believe that a pathological examination of the whole lesion should also be performed in elderly patients. Furthermore, healthcare compliance of elderly patients may be low, and lack of surveillance in underdiagnosed invasive cancer or progressing DCIS may lead to the need for more invasive treatments and higher national healthcare costs due to the delay in surgical treatments (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…LVCs were more likely to use MP in selected high‐risk donors compared to HVCs where a more routine use was observed. Such differences were also seen in other surgical fields 26 and could be given by the fact that in some countries (i.e., Italy and Germany) LVCs must face the up‐front cost and financial constraints of the diagnosis‐related‐group (DRG) reimbursement, leading to limited MP use. In the French PERPHO study, the total costs for LT with end‐ischemic HOPE were similar to those preserved with static cold storage, given the reduced length of stay and the lower postoperative complications in the HOPE group 27 .…”
Section: Discussionmentioning
confidence: 99%